Media’s Approach to Artificial Intelligence: Content Analysis of US Newspapers - Beril Han Celik (Yeni Medya, 2024)
Artificial intelligence (AI) is rapidly advancing and becoming integrated into nearly every aspect of daily life, from science, technology, transportation, healthcare to finance, education, and entertainment. As AI technologies evolve, the way the public learns about AI will be crucial for its acceptance and integration into society. Media can play a pivotal role not only in informing the public but also in shaping perceptions of AI, influencing whether it is viewed from a positive or negative perspective. How AI is portrayed in the media can affect the public’s understanding and willingness to embrace these technologies. Is AI presented in the media through the opportunities it offers to society, or is the focus placed on its potential challenges? Given the influential role of media in shaping public opinion, it is crucial to examine whether the portrayal of AI in news articles fosters understanding of it through a positive or negative lens. Therefore, this study focuses on how narratives in US newspapers cover the topic Artificial Intelligence (AI). The study analyzes 166 AI-related articles from three different newspapers between January 1, 2014, and December 31, 2023, using content analysis method. The research reveals a balanced portrayal of AI across the three newspapers, highlighting artificial intelligence’s potential benefits and ethical challenges. Positive narratives emphasize technological advancements and societal benefits, while negative narratives focus on ethical concerns such as privacy and surveillance issues.